(untitled) (Islas, 2018)
El objetivo de la presente investigación es caracterizar los nuevos roles profesionales de periodistas y académicos a fin de insertar a la prensa cubana en el proceso de convergencia periodística, en correspondencia con el sistema social cubano. Se establecen cuatro principios elementales que deben acompañar la integración de redacciones en el contexto cubano actual. Se determina cómo la implementación de la convergencia periodística no es un proceso puramente organizativo, sino que requiere transformaciones inherentes a la cultura profesional de los periodistas, la concepción del mensaje y las relaciones entre los medios y el sistema político. The objective of the present research is to characterize the new professional roles that journalists and academics in order to insert the Cuban press in the process of journalistic convergence, in accordance with the Cuban social system. Four basic principles are established that must accompany the integrated newsrooms in the current Cuban context. It is determined how the implementation of journalistic convergence should not be seen as a purely organizational process, but requires transformations inherent in the professional culture of journalists, the conception of the message and the relations between the media and the political system.